Bajidor Kahot Dance in the Embassy Got Talent Competition as a Representation of Indonesian Cultural Identity in International Internship Program - Ramadin, Deajeng; Sekti, Retnayu Prasetyanti (Solah, 2025)
Abstract: The phenomenon of the International Internship Program at the Indonesian Embassy in Manila is an interesting subject for research, particularly in terms of the implementation of training and traditional dance performances. The focus of attention is on the involvement of students as trainers and dancers, as well as the role of the Bajidor Kahot dance in strengthening the cultural identity of Indonesian citizens residing in the vicinity of the Indonesian Embassy in Manila. The purpose of this paper is to describe the training process and presentation of the Bajidor Kahot dance in the Embassy Got Talent competition and other artistic activities during the program. This research uses a qualitative descriptive approach with a field study method based on experience. The Embassy Got Talent training process was conducted over 11 days and included training strategies such as demonstrations, drills, evaluations, and self-learning. The Bajidor Kahot dance performance was presented by three interns, featuring varied floor patterns and emphasizing strong dance elements. The performance received positive feedback from the competition judges, particularly regarding unity, costumes, and movement composition. In addition to the competition, training activities were also provided to members of the Dharma Wanita Persatuan, the Indonesian diaspora, and staff of the Indonesian Embassy in Manila. Through workshops, performances, and the use of traditional music and attire, the Bajidor Kahot dance serves as a means to strengthen the cultural identity of Indonesian citizens residing in the KBRI Manila environment. This study indicates that traditional dance training and performances during the internship program contribute to cultural preservation, emotional connection of Indonesian citizens with national culture abroad, and strengthening the representation of Indonesian cultural identity in an international context. Keyword: Bajidor Kahot Dance, Embassy Got Talent, Cultural Identity, Internship Program